Do nutrition and cash-based interventions and policies aimed at reducing stunting have an impact on economic development of low-and-middle-income countries? A systematic review - Nathaly Aguilera Vasquez; Jana Daher (BMC, 2019)
Abstract Background Childhood stunting is the most common manifestation of chronic malnutrition. A growing body of literature indicates that stunting can have negative repercussions on physical and cognitive development. There are increasing concerns that low- and middle-income countries (LMICs) are particularly susceptible to adverse consequences of stunting on economic development. The aim of this review is to synthesize current evidence on interventions and policies that have had success in reducing stunting and explore the impact of successes on economic indicators. Methods This review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles were searched through MEDLINE via PubMed and Ovid, Cochrane Library, Web of Science and ProQuest. Only articles that addressed the effects of nutrition and cash-based interventions and/or policies on stunting and reported effects on childhood mortality and/or human capital indicators were included. Two reviewers independently abstracted data and assessed quality. Results Seventeen studies from Africa (47%), South America (41%), and South Asia (12%) met the eligibility criteria: 8 cohort studies, 4 case studies, 4 Randomized Control Trials (RCTs) and 1 quasi-trial. Three types of interventions/policies were evaluated: multisectoral policies, nutritional supplementations and cash-based interventions (CCT). Overall, 76% of the included studies were successful in reducing stunting and 65% of interventions/policies reported successes on stunting reductions and economic successes. Five of the 11 successful studies reported on nutritional supplementation, 4 reported on multisectoral policies, and 2 reported on CCT interventions. Average Annual Rate of Reduction (AARR) was calculated to assess the impact of multisectoral policies on childhood mortality. AARR for under 5 mortality ranged from 5.2 to 6.2% and all countries aligned with the global target of 4.4% AARR. Quality assessment yielded positive results, with the biggest concerns being attrition bias for cohort studies, blinding for trials and generalizability of results for case studies. Conclusions Evidence suggests that investment in fighting chronic malnutrition through multisectoral policies, multi-year nutritional supplementation (protein or multiple micronutrient supplementation) and possibly CCTs can have a long-term impact on economic development of LMICs. More evidence is needed to inform practices in non-represented regions while prioritizing standardization of economic indicators in the literature.